Enhancement of Electrocatalytic Performance in Ceo2–V2o5–Rgo Heterojunction Nanocomposites as a Bi-Functional Catalyst for Oer and Her in the Alkaline Medium - Ruiz-Leon, D; Ruiz-Leon, D (Springer Science and Business Media Deutschland GmbH, 2025)
The generation of hydrogen through the electrocatalytic water-splitting process is pivotal for the establishment of hydrogen economy. Yet, there remains a need to focus on abundant and non-toxic materials for this process to become more efficient and less polluting. In this study, we developed a low-cost, less toxic and bi-functional CeO2–V2O5–rGO (CVR) heterojunction nanocomposite electrocatalyst. Its performance is comparable to the benchmark Ni plate in a 1-M KOH solution, and it can be prepared via a straightforward solvothermal method at the lower temperatures. The newly synthesized electrocatalyst exhibits the remarkable performance in the overall water-splitting as a bi-functional electrocatalyst in the alkaline electrolyte medium. The onset potential of the CVR heterojunction nanocomposite for the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) is 1.75 and − 0.323 V versus reversible hydrogen electrode (RHE), respectively. A key significant finding of our research is that the reduced graphene oxide (rGO) considerably enhances the electronic conductivity of the bi-metallic oxides, leading to the efficient hydrogen production and moving us one step closer to an ideal platform for catalytic processes. Our work not only points toward the direction of efficient catalysts and improved the electrocatalytic performance of the two semiconductor nanomaterials with rGO but also offers an effective model for an in-depth mechanistic understanding of the electrochemical water-splitting. © The Author(s), under exclusive licence to the Institute of Chemistry, Slovak Academy of Sciences 2025.